Traumatic Brain Injury Dysregulates MicroRNAs to Modulate Cell Signaling in Rat Hippocampus - Liu, Liang; Sun, Tingyi; Liu, Zilong; Chen, Xiaorui; Zhao, Lili; Qu, Guoqiang; Li, Qingjie (PloS one, 2014)
Traumatic brain injury (TBI) is a common cause for cognitive and communication problems, but the molecular and cellular mechanisms are not well understood. Epigenetic modifications, such as microRNA (miRNA) dysregulation, may underlie altered gene expression in the brain, especially hippocampus that plays a major role in spatial learning and memory and is vulnerable to TBI. To advance our understanding of miRNA in pathophysiological processes of TBI, we carried out a time-course microarray analysis of microRNA expression profile in rat ipsilateral hippocampus and examined histological changes, apoptosis and synapse ultrastructure of hippocampus post moderate TBI. We found that 10 out of 156 reliably detected miRNAs were significantly and consistently altered from one hour to seven days after injury. Bioinformatic and gene ontology analyses revealed 107 putative target genes, as well as several biological processes that might be initiated by those dysregulated miRNAs. Among those differentially expressed microRNAs, miR-144, miR-153 and miR-340-5p were confirmed to be elevated at all five time points after TBI by quantitative RT-PCR. Western blots showed three of the predicated target proteins, calcium/calmodulin-dependent serine protein kinase (CASK), nuclear factor erythroid 2-related factor 2 (NRF2) and alpha-synuclein (SNCA), were concurrently down- regulated, suggesting that miR-144, miR-153 and miR-340-5p may play important roles collaboratively in the pathogenesis of TBI-induced cognitive and memory impairments. These microRNAs might serve as potential targets for progress assessment and intervention against TBI to mitigate secondary damage to the brain.